(untitled) (Palíndromo, 2022)
The essay adresses the creation of artist books as devices that help to systematize my research into visual arts, presenting itself as a way of visual mapping of the creative process, creating clues and possible paths for reflection. Starting from Warburg’s methodological approach, when organizing his elliptical library (Warburg Library, currently Warburg Institute) or creating his Atlas Mnemosyne based on the principle of “Law of good neighborhood”, taking into account the ability of books or images to relate to each other without the need for an organization as obvious or linear, such as chronological or by the name of the authors. In this way, starting from the juxtaposition of images, my creation and works by artists who are a reference in my process. I present four artist’s books that account for four axes of discussion, within my creative process, which will be presented succinctly in this article, as the central objective will be the discussion of the methodology adopted in the organization of the work itself, through the artist’s books, as well as a discussion about the challenges of conducting a research in the area of the creative process. Keywords: Artist’s book; visual mapping; creative process.